The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0954406220910176
|View full text |Cite
|
Sign up to set email alerts
|

Study of turbulent flow past a square cylinder using partially-averaged Navier–Stokes method in OpenFOAM

Abstract: The present paper reports numerical simulation of turbulent flow over a square cylinder using a novel scale resolving computational fluid dynamics technique named Partially-Averaged Navier–Stokes (PANS), which bridges Reynolds-Averaged Navier–Stokes (RANS) with Direct Numerical Simulation (DNS) in a seamless manner. All stream-wise and wall normal mean velocity components, turbulent stresses behavior have been computed along the flow (streamwise) as well as in transverse (wall normal) direction. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…As the angle of attack of downstream hydrofoil increases, it was observed that free surface waves become more non-linear. For the simulated highly nonlinear cases, the wave steepness ratio is found to be the order of 0.2618 for 2°of angle of attack and 0.3979 for 8°of angle of attack as calculated in equations ( 5) and (6).…”
Section: Effect Of Angle Of Attack Of the Downstream Hydrofoilmentioning
confidence: 80%
See 3 more Smart Citations
“…As the angle of attack of downstream hydrofoil increases, it was observed that free surface waves become more non-linear. For the simulated highly nonlinear cases, the wave steepness ratio is found to be the order of 0.2618 for 2°of angle of attack and 0.3979 for 8°of angle of attack as calculated in equations ( 5) and (6).…”
Section: Effect Of Angle Of Attack Of the Downstream Hydrofoilmentioning
confidence: 80%
“…In Einstein notation, the unsteady RANS equations for three-dimensional, unsteady turbulent flow of an incompressible fluid can be written as 6,34,35,41 :…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…These examples include three types of models, namely, 2D unsteady Reynolds-averaged simulations (URANS), 3D LES/RAS, and 3D improved delayed detached eddy simulations (IDDES) [18]. Moreover, the following techniques provide added elements to the discussion: the Spalart-Allmaras model and DES [19], LES and the Smagorinsky model [20][21][22], VLES [23], and partially averaged Navier-Stokes (PANS) simulations [24,25].…”
Section: Introductionmentioning
confidence: 99%